An autofocus algorithm considering wavelength changes for large scale microscopic hyperspectral pathological imaging system. Issue 5 (30th January 2022) - Zhang, Qing; Wang, Yan; Li, Qingli; Tao, Xiang; Zhou, Xiufeng; Zhang, Yonghe; Liu, Gang
Abstract: Microscopic hyperspectral imaging technology has been widely used to acquire pathological information of tissue sections. Autofocus is one of the most important steps in microscopic hyperspectral imaging systems to capture large scale or even whole slide images of pathological slides with high quality and high speed. However, there are quite few autofocus algorithm put forward for the microscopic hyperspectral imaging system. Therefore, this article proposes a Laplace operator based autofocus algorithm for microscopic hyperspectral imaging system which takes the influence of wavelength changes into consideration. Through the proposed algorithm, the focal length for each wavelength can be adjusted automatically to ensure that each single band image can be autofocused precisely with adaptive image sharpness evaluation method. In addition, to increase the capture speed, the relationship of wavelength and focal length is derived and the focal offsets among different single band images are calculated for pre‐focusing. We have employed the proposed method on our own datasets and the experimental results show that it can capture large‐scale microscopic hyperspectral pathology images with high precise. Abstract : Microscopic hyperspectral imaging has been widely used in pathological diagnosis. This article proposes a Laplace operator based autofocus algorithm for microscopic hyperspectral imaging system. Through the proposed algorithm, the focal length can be adjusted automatically to ensure that each single‐band image can be autofocused precisely. In addition, the relationship of wavelength and focal length is derived to increase the capture speed. We have employed the proposed method on our own datasets and the experimental results prove its effectiveness.